Hubungan Lingkar Leher dengan Obesitas Sentral pada Mahasiswa di Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Sonia Magdalena Manurung; fitri Nur Malini Siregar; Irfan Darfika Lubis; Eka Febriyanti (UMSU, 2023)
Introduction: Central obesity is the biggest challenge that occurs in developing countries in the world. Even central obesity is also increasing in all age groups and genders. Neck circumference is one of the new anthropometric methods to determine central obesity. Neck circumference can describe the storage area for upper body fat which is significantly related to disease risk factors. Objective: To analyze the relationship between neck circumference and central obesity in students at the Faculty of Medicine, University of Muhammadiyah North Sumatra batch 2019. Methods: This research method is a descriptive analytic study with a cross sectional approach. The research subjects were 135 students of the Faculty of Medicine, University of Muhammadiyah North Sumatra, batch 2019 consisting of men and women who met the inclusion and exclusion criteria. The data is processed using SPSS which is tested for normality using the Kolmogorov Smirnov test, then the data will be carried out by the Pearson test, if one or both variables are not normally distributed, then the Spearman test is performed. Results: Neck circumference with waist circumference in male samples obtained p value 0.01 and r value = 0.565. Neck circumference with waist circumference in female samples obtained p value 0.01 and r value = 0.531. Conclusion: There is a relationship between neck circumference and central obesity (waist circumference) in students at the Faculty of Medicine, University of Muhammadiyah North Sumatra, class of 2019 with a p value 0.01, moderate closeness and